Temporal regulation of planar cell polarity: insights from the Drosophila eye. - Schweisguth, F. (Cell, 2005)
In this issue of Cell, identify a first regulatory link between planar cell polarity (PCP) signaling and apical-basal polarity. The authors propose that a component of the apical Crumbs complex regulates the phosphorylation of the Frizzled (Fz) PCP receptor, thus modulating PCP in the Drosophila eye.